DEVELOPMENT OF EDUCATION AND TRAINING: MODERN TRENDS - Паламарчук, О. Ф. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2017)
The article is devoted to analyzing the development of learning and teaching in higher education and the analysis of modern trends. The peculiarities of the development of learning and teaching in European higher education documents are analyzed. The paper focuses on the European principles of teaching and learning, the transition from research to improving the quality of teaching and the use of cutting-edge teaching and learning technologies. There is a tendency to change the teaching concept (balance between teaching and research, attracting external stakeholders, requirements for teaching staff) due to the diversity of students (disabiled students, mature students), internationalization (international teachers, students and teaching in English) and e-learning (the use of portable technologies, 3D printing and gamification)